Meteor Radar Estimations of Gravity Wave Momentum Fluxes: Evaluation Using Simulations and Observations Over Three Tropical Locations. Issue 8 (17th August 2019) - Pramitha, M.; Kishore Kumar, K.; Venkat Ratnam, M.; Rao, S. Vijaya Bhaskara; Ramkumar, Geetha
Abstract: Meteor radars are widely used to study gravity wave (GW) variances and their momentum fluxes at the altitudes where meteor counts are sufficient to yield good statistical fits to the data. These radars provide hourly zonal and meridional wind observations round the clock in 80‐ to 100‐km height domain. However, the capability of meteor radars in estimating GW momentum fluxes should be evaluated before they can be used for any research applications. In this regard, the present study evaluates the meteor radar observations of GW momentum fluxes obtained from Thumba (8.5°N, 77°E; 2006–2015), Kototabang (0.2°S, 100.3°E; 2002–2017), and Tirupati (13.63°N, 79.4°E; 2013–2018) using three‐dimensional wind field simulations, which include specified tidal, planetary and GW fields. A modified composite day analysis is adopted to estimate the GW momentum fluxes, which also accounts for the tidal and planetary wave contributions. The results showed that the retrieved and specified GW momentum fluxes agree very well over Tirupati followed by Thumba and Kototabang. It is noted that the agreement between the retrieved and simulated fields depend on the number of meteor detections used in the analysis. After evaluating the meteor radar retrieved GW momentum fluxes by employing simulations, their interannual variability and climatologies over the three observational locations are constructed. The significance of the present study lies in evaluating the capability of three meteor radars located in equatorial and low‐latitudes in estimating GW momentum fluxes by employing three‐dimensional wind field simulations with specified mean winds, tidal, planetary, and GW fields. Key Points: Evaluation of meteor wind radars operating at low and equatorial latitudes in estimating the MLT region gravity wave momentum fluxes Three‐dimensional wind simulations with specified mean, tidal, planetary, and gravity wave amplitudes Climatology of zonal and meridional gravity wave momentum fluxes in the MLT region over low and equatorial latitudes